Fatal paraphenylenediamine poisoning due to black henna - Şık, Güntülü; Çıtak, Agop (The Turkish Journal of Pediatrics, 2016)
Paraphenylenediamine (PPD) is an oxidative chemical allergen that can cause hypersensitivity reactions. PPD intoxication could cause severe systemic adverse effects like acute renal failure, rhabdomyolysis and multiple organ failure. In this text we present a 9 year-old female patient who developed multiple organ failure and cardiac arrhythmia as a result of extensive application of PPD added to henna to the skin. Plasma exchange (PE) and continuous venovenous hemodiafiltration (CVVHDF) were started. The patient died on day 4 after developing ventricular fibrillation that was resistant to antiarrhythmic treatment and defibrillation. In summary, the most commonly seen clinical signs in PPD intoxication are cervical, upper respiratory and muscle edema, intravascular hemolysis, rhabdomyolysis, severe cardiac arrhythmias and acute renal failure. These symptoms would be suggestive of PPD poisoning.
Keywords: hemodiafiltration; henna; paraphenylenediamine; pediatric intensive care; plasma exchange